A new thermodynamic description of the binary Sb – Zn system. - Gierlotka, Wojciech (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
The Sb – Zn alloys are important from technological point of view. Antimony – zinc alloys are not only part of lead-free solders but also thermoelectric materials. A good thermodynamic description of this system is essential for further investigations of multi-components materials that include Sb and Zn. A new assessment was proposed in this work based on recently published experimental reports. Good agreement between calculations and experiments was found. Moreover, two models were used for describing the liquid phase: substitutional solution and associated solution.